Novel intelligent corn thresher - MENG JING (2017)
The utility model discloses a novel intelligent corn thresher, which comprises a frame, corn stalk feeding barrel, go up the cover, a feeding section of thick bamboo, frame one side upper end is provided with corn stalk feeding barrel, the frame top is provided with the cover, it is provided with a feeding section of thick bamboo to go up the cover, frame one side is provided with shift knob, the frame openly is provided with the display screen, the frame below is provided with the 12V battery, it is provided with the screen cloth to go up the cover below, it is provided with solar cell panel to go up the cover surface, it is provided with the camera to go up cover one side, it is provided with the pivot to go up cover inside, pivot one end is provided with from the driven pulleys, the last area that is provided with of from the driven pulleys, the frame below is provided with the motor, motor one end is provided with driving pulley. Beneficial effect lies in: the utility model discloses compact structure not